Analyticity and uniqueness of the fractional electromagnetic boundary value problem - Ali A.R.; Jan R.; Alotaibi H.; Yaseen N.A. (American Institute of Mathematical Sciences, 2025)
This paper introduces a new study that examines the unique and analytical nature of the fractional solution to a fractional electromagnetic boundary value problem (BVP). This specific BVP is characterized by defining the tangential electromagnetic components. It has been proven that the analytical expressions for the fractional electromagnetic fields E, E?, H, and H? do not vanish in any subregions o or ? o. Furthermore, the unique solution makes E = E? and H = H? without singular fields at same region of the space. Analyticity of the fractional time-harmonic electromagnetic field within lossy or lossless dielectric regions is proven. Keyword. ? 2024 the Author(s), licensee AIMS Press.